Caracterización y repercusión de la enfermedad periodontal en perros ( canis lupus familiaris ) mayores a 6 años - Lema Buñay, Edwin Leonardo (Machala : Universidad Técnica de Machala, 2018)
Periodontal disease is a pathology of chronic and multifactorial origin, caused by the infiltration of bacteria in the gingival pockets, the bacteria are initially aerobic and facultative anaerobes Gram + ("Streptococcus spp, Actinomyces spp., And Lactobacillus spp) and Gram (-) ( Neisseria spp, Campylobacter spp) and later they are anaerobic Gram + and negative ( Peptostreptococcus spp, Fusobacterium spp, Spirochetes among others), which affect the canine and feline species with a percentage of between 60-80% of the population. Among its diagnostic methods, we highlight the evaluation of the plaque, tartar, the depth of the gingival sulcus, the bleeding of the gums, dental movement, radiographic tests, bacterial culture, blood count, among others. Its main treatment is based on the removal and total cleaning of dental plaque and tartar, scaling, polishing, surgical treatment in severe cases accompanied by a pharmacological treatment based on the use of antibiotics such as: imipenem, Amoxicillin plus Ac. Clavulanic, doxycycline, chloramphenicol, among others. Following the context, this bibliographical research focuses on the characterization and repercussion that this pathology can cause to the organism of the animal, emphasizing the systemic effects produced by affecting other organs among them; heart (bacterial endocarditis), liver (hepatitis), kidney (glomerulonephritis), etc. Its prevention is based on the brushing of the oral cavity, use of toys that allow the removal of tartar, avoid the consumption of soft foods and finally mention is made of the periodic revision of the oral cavity by the veterinarian.
La enfermedad periodontal es una patología de origen crónico y multifactorial, causada por la infiltración de bacterias en las bolsas gingivales, las bacterias inicialmente son aerobias y anaerobios facultativos Gram+ (“Streptococcus spp, Actinomyces spp. , y Lactobacillus spp) y Gram(-) ( Neisseria spp, Campylobacter spp) y después son anaerobias Gram+ y negativos ( Peptostreptococcus spp, Fusobacterium spp, Spirochetes entre otros), que afectan a la especie canina y felina con un porcentaje de entre 60-80% de la población. Entre sus métodos diagnósticos resaltamos la valoración de la placa, del sarro, la profundidad del surco gingival, el sangrado de las encías, movimiento dental, pruebas radiográficas, cultivo bacteriano, hemograma, entre otros. Su tratamiento principal se basa en la remoción y limpieza total de la placa dental y el sarro, raspado, pulido, tratamiento quirúrgico en casos severos acompañado de un tratamiento farmacológico basado en el uso de antibióticos tales como: el imipenem, Amoxicilina más Ac. Clavulánico, doxiciclina, cloranfenicol, entre otros. Siguiendo el contexto, esta investigación bibliográfica se enfoca en la caracterización y la repercusión que esta patología puede provocar al organismo del animal, recalcando los efectos sistémicos que produce afectando otros órganos entre ellos; corazón (endocarditis bacteriana), hígado (hepatitis), riñón (glomerulonefritis), etc. Su prevención se basa en el cepillado de la cavidad oral, uso de juguetes que permitan la remoción del sarro, evitar el consumo de alimentos blandos y por último se menciona la revisión periódica de la cavidad bucal por parte del médico veterinario.
Keywords: GINGIVITIS; ENFERMEDAD; CAVIDAD; ORAL